Effects of Cholesterol Extraction Process and Fat and Whey Protein Additions on Ice Cream Mixes - Hidalgo, María Eugenia (2019)
The aim of this work was to evaluate the cholesterol extraction process in ice cream mixes (ICMs) by using β-cyclodextrin (βCD) and to analyze the effect of this extraction on the ICM rheological, stability, and sensory characteristics. The effects of fat and whey protein (WP) additions on ICM stability were also evaluated. The maximum percentage obtained for cholesterol extraction was 93.6%. The flow curves indicated that ICM showed a thixotropic behavior before and after cholesterol extraction, which was enhanced when the fat content and/or percentage of βCD increased. The stability of ICM with cholesterol-reduced content (RCho-ICM) was influenced by the fat content and/or the presence of WP. The RCho-ICM with the highest fat and/or WP addition showed less tendency to melt and had the smallest amount of accumulated molten liquid. These latter ICMs presented the slowest melting rates. Also, RCho-ICMs proved to be more stable than ICMs. RCho-ICM samples obtained with a ratio of βCD/fat content of 1% w/w were evaluated by a trained sensory panel. In addition, an acceptability test of the sample with better sensory attributes was conducted.